Geographic variation of Africanized honey bees (Apis mellifera L.) in Brazil: Multivariate morphometrics and racial admixture - Diniz-Filho, José Alexandre Felizola; Malaspina, Osmar [UNESP] (My University, 1996)
The correspondence between morphometric and isozymic geographic variation patterns of Africanized honey bees in Brazil was analyzed. Morphometric data consisted of mean vectors of 19 wing traits measured in 42 local populations distributed throughout the country. Isozymic data refer to allelic frequencies of malate dehydrogenase (MDH), and were obtained from Lobo and Krieger. The two data sets were analyzed through canonical trend surface, principal components and spatial autocorrelation analyses, and showed north-south dines, demonstrating that Africanized honey bees in southern and southeastern Brazil are more similar to European honey bees than those found in northern and northeastern regions. Also, the morphometric variation is within the limits established by the racial admixture model, considering the expected values of Africanized honey bee fore wing length (WL) in southern and northeastern regions of Brazil, estimated by combining average values of WL in the three main subspecies involved in the Africanization process (Apis mellifera scutellata, A. m. ligustica and A. m. mellifera) with racial admixture coefficients.
Keywords: isoenzyme; malate dehydrogenase; brazil; enzyme polymorphism; forelimb; gene frequency; geographic distribution; honeybee; morphometrics; multivariate analysis; nonhuman; population genetics